THE COLORIMETRY WITH A HIGH DIMENSIONAL RESOLUTION - I. E. Zuikov; E. N. Savkova (Приборы и методы измерений)
The developed method of Objects photometric and colorimetric characteristics measurements on the base of digital cameras are described. Application of the initial samples those are realized as the support of the control points on a non-radiant Object or as primary sources on a radiant Object will provide the metrological traceability and also build a conditional scale in each colour channel and expand the dynamic range of measurements by increasing the reliability and accuracy of measurement results.